2020
DOI: 10.1039/d0cp04160b
|View full text |Cite
|
Sign up to set email alerts
|

Tunable electronic properties and Schottky barrier in a graphene/WSe2 heterostructure under out-of-plane strain and an electric field

Abstract: Tuning the electrical transport behavior and reducing the Schottky barrier height of nanoelectronic devices remain a great challenge. To solve this issue, the electronic properties and Schottky barrier of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…The optimum spacing for pattern a is 3.5 Å and the optimum spacing for patterns b and c is 3.6 Å at their lowest binding energy. This result shows that graphene and AlP are mainly combined through the vdW force, and the interlayer spacing is close to that of typical vdW heterostructures such as graphene/MoS 2 [35], graphene/WSe 2 [36] and graphene/InTe [37]. Meanwhile, this further confirms that pattern a has the lowest binding energy and smallest layer spacing compared with patterns b and c. Therefore, we will focus on pattern a hereafter.…”
Section: Structural Stability Of Graphene/alp Heterostructuressupporting
confidence: 70%
“…The optimum spacing for pattern a is 3.5 Å and the optimum spacing for patterns b and c is 3.6 Å at their lowest binding energy. This result shows that graphene and AlP are mainly combined through the vdW force, and the interlayer spacing is close to that of typical vdW heterostructures such as graphene/MoS 2 [35], graphene/WSe 2 [36] and graphene/InTe [37]. Meanwhile, this further confirms that pattern a has the lowest binding energy and smallest layer spacing compared with patterns b and c. Therefore, we will focus on pattern a hereafter.…”
Section: Structural Stability Of Graphene/alp Heterostructuressupporting
confidence: 70%
“…The previous work showed that the interfacial contact properties of the heterostructure are closely related to the performance of devices . Here, the lattice matching and proper energy band position are the key parameters that affect the structural stability and charge-transfer efficiency of the system.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that E ⊥ is of great value in adjusting the E g of the 2D structure. 46,47 Compared with the HSE06 method, the PBE method can conveniently obtain almost the same theoretical band trend (refer to Table 1 and Table S1, ESI†). Therefore, we use the PBE method to explore the electronic properties of the twisted BP structure under E ⊥ , which plays a significant role in guiding future experimental research.…”
Section: Resultsmentioning
confidence: 98%